The value of emotions: recovering theological relevancy in research on emotions - Nüssel, Friederike (Philosophy, theology and the sciences, 2024)
This essay explores the conditions for developing a theology of emotions from both a historical and constructive perspective. Historically, it elucidates how the traditional emphasis on controlling passions and affects diminished when Friedrich Schleiermacher introduced the modern term Gefühl to advocate for the distinct character and anthropological necessity of religion. Despite the topic becoming increasingly neglected, Wolfhart Pannenberg revitalized the importance of affective life in the multitude of emotions as crucial for human identity development. This sets the stage for the constructive inquiry into the nature of emotions and the distinct character of religious emotions, considering challenges from neuroscience and the analysis of emotions as concern based construals by Robert C. Roberts. Roberts' cognitive understanding is integrated with Johannes Fischer's argument for the narrative foundation of moral perception, as well as a neuropsychiatric case study on the processing of narratives depicting help-requiring situations. The paper posits that by leveraging a cognitive understanding of emotions and recognizing the role of narrative, a theology of emotions can explore how religious narratives evoke and shape emotions and perceptions.